1996
DOI: 10.1083/jcb.132.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid and bFGF control different modes in proliferating myoblasts.

Abstract: Abstract. Myogenic cells provide excellent in vitro models for studying the cell growth and differentiation. In this study we report that lysophosphatidic acid (LPA), a bioactive phospholipid contained in serum, stimulates the growth and inhibits the differentiation of mouse C2C12 myoblast cells, in a distinct manner from basic fibroblast growth factor (bFGF) whose mitotic and anti-differentiation actions have been well investigated. These actions of LPA were both blocked by pertussis toxin, suggesting the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 77 publications
3
51
1
Order By: Relevance
“…Conversely, transient transfection of young SCs with either S100B or a dominant negative RAGE mutant resulted in the acquisition of an aged phenotype. We also noted a remarkably reduced ability of aged SCs to secrete bFGF and S100B, which are both potent stimulators of myoblast proliferation (Riuzzi et al 2006b;Yoshida et al 1996), and we found that treatment of aged SCs with either bFGF or S100B or with conditioned medium from young SCs resulted in a nearly complete restoration of the proliferation potential along with an enhanced differentiation when aged SCs were shifted to DM. Thus, it is tempting to speculate that the reduced ability of aged SCs to release bFGF and/or S100B is a one major cause of defective proliferation (i.e., expansion), which is essential for the attainment of the critical cell density necessary for subsequent myotube formation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Conversely, transient transfection of young SCs with either S100B or a dominant negative RAGE mutant resulted in the acquisition of an aged phenotype. We also noted a remarkably reduced ability of aged SCs to secrete bFGF and S100B, which are both potent stimulators of myoblast proliferation (Riuzzi et al 2006b;Yoshida et al 1996), and we found that treatment of aged SCs with either bFGF or S100B or with conditioned medium from young SCs resulted in a nearly complete restoration of the proliferation potential along with an enhanced differentiation when aged SCs were shifted to DM. Thus, it is tempting to speculate that the reduced ability of aged SCs to release bFGF and/or S100B is a one major cause of defective proliferation (i.e., expansion), which is essential for the attainment of the critical cell density necessary for subsequent myotube formation.…”
Section: Discussionsupporting
confidence: 50%
“…As the proliferation rate is strongly affected by mitogenic factors in the medium, some of which are being secreted by myoblasts themselves, we decided to verify if aged SCs maintain the ability to respond to mitogens. To address this point, bFGF or S100B, two factors reported to stimulate myoblast proliferation via activation of ERK1/2 signaling (Riuzzi et al 2006b;Yoshida et al 1996), were added to young and aged SCs cultured in medium containing 2% FBS, and the cells were then tested for BrdU incorporation (Fig. 8a).…”
Section: Young and Aged Scs Show Differential Expression Of Ragementioning
confidence: 99%
“…Though highmitogen growth medium inhibits myogenesis, a low rate of differentiation can be detected in highly confluent cultures of C2C12 cells (6,58). Induction of Akt was also detected under these conditions, but it occurred more slowly than in differentiation medium (compare Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Stimulation of PC12 cells with FGF-2 induces differentiation via sustained activation of the Erks, which is mediated by recruitment of SHP-2 to FRS-2␣ (17). In contrast, the FGFR signaling pathway engaged by myoblasts suppresses myogenesis (8,29,57,63,73). It remains to be established whether SHP-2 participates downstream of the FGFR in myoblasts to mediate entry into myogenesis.…”
mentioning
confidence: 99%